Input-output analysis of energy: an application to Indian economy (1979-80 to 1991-92) - Dash, U.K.; Saxena, K.K. (1999)
In this article an attempt has been made to apply hybrid units formulation of energy input-output analysis for the energy intensity variations in the different sectors of the economy for a period of ten years i.e. from 1979-80 to 1991-92. The analytical results indicate that about 56 per cent of the economic sectors showed remarkable downward trend in the total primary energy intensity, implying the effectiveness of energy conservation measures. - Reproduced
Keywords: Energy resources